2000
DOI: 10.1086/315696
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Thymidine Kinase from Acyclovir‐Resistant and ‐Susceptible Herpes Simplex Virus Type 1 Isolated from Bone Marrow Transplant Recipients

Abstract: Emergence of acyclovir (Acy)-resistant herpes simplex virus (HSV) is a major concern in bone marrow transplant recipients. Phenotypic and genetic characterization of thymidine kinase (TK) was done for 7 Acy-susceptible and 11 Acy-resistant HSV-1 isolated from 11 patients. In total, 19 amino acid substitutions were detected that were not related to Acy resistance but to TK gene polymorphism, including 5 mutations that have not been previously reported. The Acy-resistant strain from 1 patient presented no TK gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 15 publications
4
77
0
Order By: Relevance
“…Isolate 6b also contained a mutation in the DNA pol gene conferring resistance to foscarnet (42). Isolate 7 contained a deleted A at nt 1065 and three other nonsilent mutations of which two (Pro42Leu and Arg89Gln) have been found in other pretherapy isolates from this study and elsewhere (21,25) and thus presumably are associated with gene polymorphism. Isolates 8 and 9 had deletions of G at positions 779 and 180, respectively.…”
Section: Susceptibility Of Hsv Clinical Isolates To Acvmentioning
confidence: 64%
See 4 more Smart Citations
“…Isolate 6b also contained a mutation in the DNA pol gene conferring resistance to foscarnet (42). Isolate 7 contained a deleted A at nt 1065 and three other nonsilent mutations of which two (Pro42Leu and Arg89Gln) have been found in other pretherapy isolates from this study and elsewhere (21,25) and thus presumably are associated with gene polymorphism. Isolates 8 and 9 had deletions of G at positions 779 and 180, respectively.…”
Section: Susceptibility Of Hsv Clinical Isolates To Acvmentioning
confidence: 64%
“…Furthermore, Sasadeusz et al have identified mutational hot spots consisting of frameshift mutations within homopolymer nucleotide stretches of G's and C's (41). Recent studies by our group (16) and others (25) have demonstrated that about 50% of the clinical ACV-resistant strains contain an insertion or a deletion of one or two nucleotides in homopolymer runs of G's and C's, whereas the other half presents single-base substitutions in conserved or nonconserved regions of the TK gene.…”
mentioning
confidence: 98%
See 3 more Smart Citations